Respostas
respondido por:
3
Resposta:
-5 e 2
Explicação passo-a-passo:
Pela soma e produto temos:
Podemos perceber que as raízes são: e
respondido por:
1
Oie, Td Bom?!
• Resposta: Opção A.
f(x) = x² + 3x - 10 ⇐ f(x) = 0.
0 = x² + 3x - 10
x² + 3x - 10 = 0
x² + 5x - 2x - 10 = 0
x . (x + 5) - 2(x + 5) = 0
(x + 5) . (x - 2) = 0
x + 5 = 0 ⇒ x = - 5
x - 2 = 0 ⇒ x = 2
S = {x₁ = - 5 , x₂ = 2}
Att. Makaveli1996
Perguntas similares
5 anos atrás
5 anos atrás
5 anos atrás
7 anos atrás
7 anos atrás
7 anos atrás
8 anos atrás
8 anos atrás
8 anos atrás